Aging of biomixtures: Effects on carbofuran removal and microbial community structure - Castro Gutiérrez, Víctor Manuel (2017)
The aim of this work was to determine the efficiency of a straw/compost/soil biomixture for pesticide depuration during its aging and continuous use, for a period of over a year, based on its capacity to remove carbofuran (CFN), while simultaneously monitoring the variations in microbial community structure. Successive CFN spikings were applied in the biomixture at 6-week intervals, and the removal efficiency was determined 48 h post-application. Initially, only a discrete degradation performance was observed (9.9%), but one CFN application was sufficient to induce efficient elimination (>88.5%) of the pesticide at subsequent influxes for a period of over 6 months. A statistically significant reduction on CFN removal efficiency after this time was detected, reaching levels similar to the fresh-prepared biomixture (14.8%) at the end of the experiment. Simultaneous DGGE analyses showed only modest changes on microbial community patterns through time for both, bacteria and fungi. The clustering of genetic fingerprints in chronological groups corresponding to significantly different CFN degradation efficiencies indicates that biomixture aging changes not only the composition of microbial communities, but also their suitability to engage in pesticide degradation. Periodic substitution of straw/compost/soil biomixture in biopurification systems or regular provision of easily-degradable organic substrates should be considered to maintain an adequate depuration capacity on this system.